2018
DOI: 10.1080/14763141.2018.1535617
|View full text |Cite
|
Sign up to set email alerts
|

The effect of landing surface on landing error scoring system grades

Abstract: Different landing surfaces may affect lower extremity biomechanical performance during athletic tasks. The magnitude of this effect on clinical screening measures such as jump-landings is unknown. This study determined the effect of court (CS), grass (GS), and tile (TS) surfaces on Landing Error Scoring System (LESS) grades. A repeated-measures design was used. Forty (21F, 19M; mean age = 23.8 ± 2.4 yr) recreational athletes performed a jump-landing task on three different landing surfaces. 2D videography reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Studies documenting a sex effect on movement technique using the LESS report worse (higher) total scores in women vs. men (4,7,21,34,42). This finding is not unanimous (3,20,22) and the sex effect on movement technique has recently been questioned with the exception of women landing with greater knee valgus (2). Those reporting a sex effect using the LESS commonly conducted the testing on flooring consisting largely of concrete material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies documenting a sex effect on movement technique using the LESS report worse (higher) total scores in women vs. men (4,7,21,34,42). This finding is not unanimous (3,20,22) and the sex effect on movement technique has recently been questioned with the exception of women landing with greater knee valgus (2). Those reporting a sex effect using the LESS commonly conducted the testing on flooring consisting largely of concrete material.…”
Section: Discussionmentioning
confidence: 99%
“…Although epidemiological data present conflicting results regarding injury risk and athletic surface type, differences in movement technique among athletic surfaces merit scientific inquiry. Only one study examined the effects of athletic surface type on overall LESS scores and found no differences across tennis court, grass, and tile surfaces or between sexes (20). However, this study failed to adequately control for muscle soreness and fatigue which has been shown to influence lower extremity movement technique in both men and women (4,13,14,28,44).…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen studies compared LESS scores between males and females (Table 1). Six studies found females to have significantly higher overall LESS scores compared to males 1,32,40,46,52,56 , six studies found no significant difference in overall scores between sexes 5,6,8,45,57,69 , and the remaining two studies did not specify if the differences were significant 14,70 . Thirty studies reported overall LESS scores separately for males (n = 3294) and females (n = 1910), with resulting weighted mean scores for males of 5.0 ± 1.8 and 5.6 ± 1.7 errors for females.…”
Section: Sexmentioning
confidence: 97%
“…The NOS adapted for cross-sectional studies was used for 33 (64%) studies. Out of a maximum of 10 stars, 2 studies scored two stars 35,39 , 4 studies four stars [40][41][42][43] , 7 studies five stars [44][45][46][47][48][49][50] , 10 studies six stars 1,18,32,37,38,[51][52][53][54][55] , 2 studies seven stars 56,57 , 7 studies eight stars 4,5,19,33,[58][59][60] , and 1 study nine stars 6 . The RoB 2 was used for 9 (17%) studies.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 1 more Smart Citation